Effects of community health worker–led interventions on cardiometabolic outcomes in vulnerable populations: A systematic review and meta-analysis - Ismaila Ajayi Yusuf; Ihesiulo Alozie; Micah Nnabuko Okwah; Vikash Kumar; Zubeda Idris-Saeed; Hakeem Popoola; Emmanuel Babawale; Daniel Adepoju; Ayotunde Famokunwa; Omolaso Oluwabamise (PLOS Global Public Health, 2026)
Cardiometabolic diseases (CMDs) disproportionately affect vulnerable populations worldwide. Community health worker (CHW)–led interventions may reduce risk and improve preventive care, but their effectiveness remains unclear. This systematic review and meta-analysis evaluated their effectiveness on cardiometabolic outcomes in vulnerable groups. A comprehensive search of PubMed/MEDLINE, Scopus, Embase, ClinicalTrials.gov, and Cochrane Library was performed from January 1, 2000 to December 20, 2025, for randomized trials of CHW-led interventions on cardiometabolic outcomes. Primary outcomes were systolic and diastolic blood pressure; secondary outcomes were body mass index (BMI), glycosylated hemoglobin (HbA1c), and low-density lipoprotein cholesterol (LDL-C). Outcomes were pooled as mean differences using the generic inverse variance method; heterogeneity was assessed using I 2 . Thirty randomized trials (15,295 participants) were included. CHW-led interventions significantly improved systolic blood pressure (WMD = −3.72 mmHg; 95% CI: −5.94 to −1.51; I 2 = 99.1%) and diastolic blood pressure (WMD = −2.22 mmHg; 95% CI: −3.50 to −0.95; I 2 = 98.6%); 95% prediction intervals crossed the null for all five outcomes (e.g., SBP: −15.12 to 7.67 mmHg), indicating uncertainty at a new site. BMI and HbA1c improved modestly but were attenuated to non-significance by trim-and-fill analysis, suggesting publication bias; LDL-cholesterol effects were not significant. SBP reductions were significant in low- and middle-income countries (LMICs) (WMD = −5.09 mmHg; 95% CI: −7.57 to −2.60) but not high-income countries (HICs), with the largest effects in Africa. GRADE certainty was low for blood pressure, moderate for BMI, very low for HbA1c, and low for LDL-cholesterol. CHW-led interventions modestly improve cardiometabolic outcomes in vulnerable populations, with low-to-very-low certainty evidence for blood pressure and glycemic control and moderate certainty for BMI, supporting a potential role in cardiovascular risk-reduction strategies, particularly in LMICs. However, wide prediction intervals and non-significant meta-regression for intervention design features (contact frequency, duration, delivery format) warrant cautious, hypothesis-generating interpretation pending higher-quality trials. Systematic review Registration Registration Number: PROSPERO 2025 CRD420251248842